Supporting the oppressed and its evidence In the sayings of Ahl al-Bayt  (Journal of the College of Basic Education, 2022)
Praise be to God, Lord of the worlds, and prayers and peace be upon the Prophet Muhammad and his household, whom God chose for Himself and chose over His servants, whom He accepted for His religion and singled out for His knowledge, and exalted them with His dignity and covered them with His mercy, and raised them with His grace and raised them to His kingdom and to His good companions, and after...